Innovating Inclusive Literacy Instruction: Rethinking Single-Method Approaches for Learners with Diverse Abilities - Hussein Hussein; Miriam Maganga (Universitas Negeri Surabaya, 2025)
Reading instruction plays a crucial role in shaping learners’ academic achievement, language development, and long-term cognitive outcomes. However, in many multilingual and low-resource educational settings, teaching approaches remain dominated by a single method, often phonics-only or comprehension-only approaches, that fail to meet the diverse needs of learners with varied linguistic, cognitive, and socio-cultural backgrounds. This literature review aims to analyse the challenges associated with single-method reading instruction and the essential need for multifaceted, inclusive, and adaptive literacy frameworks. The study used a descriptive qualitative literature review, drawing on national and international research from 2000 to 2025. A systematic search identified 28 relevant studies, which were grouped and analysed using thematic synthesis. The themes highlight that single-method instruction limits reading comprehension, excludes learners with disabilities, and reduces learner engagement. Conversely, multifaceted approaches that integrate phonics, guided reading, vocabulary development, bilingual instruction, sociocultural relevance, and multimodal access lead to improved literacy outcomes, particularly for learners with disabilities and multilingual learners. The review concludes that adopting multifaceted literacy instruction requires stronger teacher training, improved curriculum design, and inclusive policy support.